Advanced Java EE development for Rational Application Developer 7.5 : developers' guidebook - Cole, Kameron (MC Press, 2011)
This advanced book provides a solid overview of the development of a range of core Java EE technologies, combined with a good description of the development facilities provided by IBM Rational Application Developer V7.5. Senior developers, engineers, and architects involved with Java and Java EE technologies, especially those who work with Rational Application Developer and those seeking certification at the Sun Certified Java Master Tier level or the IBM Rational Application Developer Certified Professional and Certified Advanced Professional levels, will appreciate this convenient, single re.